DEONTOLOGICAL BASES OF INCREASE OF TRUST IN THE COURT - Kanatov Алмас Канатович; Munaytbasov Нурхат Маратович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
In the article retrospectively reviewed deontological problems of increase of trust in the court. In particular, it conected SWOT analysis of strengths, weaknesses, opportunities and threats to increase trust in the court in criminal proceedings.